1995
DOI: 10.1021/bi00026a028
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of specific endothelial cell-binding properties from the procoagulant protein human factor IX into the anticoagulant protein human protein C

Abstract: A series of recombinant (r) chimeric mutants of human coagulation protein C (PC) and activated protein C (APC) containing replacements of homologous PC domains by those of human coagulation factor IX (fIX) were generated, with the intention of determining whether the specific bovine aortic endothelial cell (BAEC) receptor-binding characteristics of fIX could be incorporated into the chimeric r-PC while maintaining the essential properties of PC and APC. Using a competitive BAEC displacement assay with [125I]fI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1996
1996
1997
1997

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Moreover, a mutation of lysine to arginine at residue 5, factor IX K5R, results in a factor IX molecule that has a 3-fold increased affinity for the endothelial cell binding site. Our observation that factor IX residues 3-11 are critical for the factor IX endothelial cell interaction have recently been confirmed by Castellino's laboratory (7). They demonstrated that converting the first 11 amino acids of protein C to those of factor IX resulted in a protein C chimera that bound to endothelial cells.…”
supporting
confidence: 70%
“…Moreover, a mutation of lysine to arginine at residue 5, factor IX K5R, results in a factor IX molecule that has a 3-fold increased affinity for the endothelial cell binding site. Our observation that factor IX residues 3-11 are critical for the factor IX endothelial cell interaction have recently been confirmed by Castellino's laboratory (7). They demonstrated that converting the first 11 amino acids of protein C to those of factor IX resulted in a protein C chimera that bound to endothelial cells.…”
supporting
confidence: 70%
“…The major exception to this function of Gla domains is the binding of factor IXa to the factor IXa receptor on endothelial cells. This interaction was shown to be mediated by the Gla domain (21,22).…”
mentioning
confidence: 99%
“…While these experiments clearly identify the BAEC binding locus of fIX, not fully appreciated is the extent of participation of other regions of the Gla domain, or indeed of other domains of fIX, in contributing to the proper folding of this binding epitope (8). It was the aim of the current investigation to resolve this aspect of the problem.…”
Section: Resultsmentioning
confidence: 94%
“…Specifically, exchange of the Gla domain/HS regions of fIX with those of protein C (8) and fVII (9,11), two proteins that do not compete for fIX on BAEC, demonstrated that the chimeric proteins developed the ability to compete with fIX for BAEC binding, with IC50 values of the inhibitors being nearly equal to Kd for fIX binding to these cells. In addition, a synthetic polypeptide containing residues 1-47 of fI X interacted with BAEC with the same effectiveness as that of intact fIX (8). Interestingly, replacement of residues 1-13 of protein C with the equivalent 1-14 residues of fIX also resulted in a chimeric protein that was bound at equal strength as fIX to the binding site for this latter protein on BAEC (8), a result similar to that found for a fvII/fIX chimera (9).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation